Diels–Alder reactions between hexafluoro-2-butyne and bis-furyl dienes: kinetic versus thermodynamic control. Issue 23 (2nd February 2018) - Borisova, Kseniya K.; Nikitina, Eugeniya V.; Novikov, Roman A.; Khrustalev, Victor N.; Dorovatovskii, Pavel V.; Zubavichus, Yan V.; Kuznetsov, Maxim L.; Zaytsev, Vladimir P.; Varlamov, Alexey V.; Zubkov, Fedor I.
Abstract : The tandem [4+2] cycloaddition between hexafluoro-2-butyne and bis-furyl diens can lead to "pincer" or "domino"-adducts. Abstract : The tandem [4+2] cycloaddition between hexafluoro-2-butyne and bis-furyl dienes, like difurfuryl ester, at room temperature leads to the kinetically controlled "pincer"-adducts – annulated 4 a, 8 a -bis(trifluoromethyl)hexahydro-1, 4:5, 8-diepoxynaphthalenes. On the other hand, if these reactions proceed at 140 °C, only the thermodynamically controlled "domino"-adducts – annulated 2, 3-bis(trifluoromethyl)hexahydro-1, 4:5, 8-diepoxynaphthalenes – are formed. Therefore, a very rare and unexpected example of full kinetic and thermodynamic control in the Diels–Alder reaction is reported in this paper.